Impact of digital health on the quality of primary care for people with chronic noncommunicable diseases: A scoping review protocol - Pedro Bezerra Xavier; Ísis de Siqueira Silva; Renan Cabral de Figueiredo; Aguinaldo José de Araújo; Amanda Jéssica Bernardo da Silva; Severina Alice da Costa Uchoa (PLoS ONE, 2025)
Background Chronic Non-Communicable Diseases (NCDs) represent a significant global challenge, especially in low- and middle-income countries. The introduction of digital health in Primary Health Care (PHC) has the potential to improve the quality of care for people with NCDs by offering tools such as telemedicine, mobile applications and other information and communication technologies. The aim of this study is to identify and map global experiences of using Information and Communication Technologies (ICTs) in primary care for non-communicable diseases and assess their impact on the quality of care in PHC. Methods This study presents a scoping review protocol based on the Joanna Briggs Institute criteria and the PRISMA-ScR guidelines. The review will be carried out in nine stages, including defining the aim and research questions, developing inclusion and exclusion criteria, and searching, selecting, extracting and analyzing the evidence. The databases consulted include MEDLINE/PubMed, JBI Evidence Synthesis and Open Science Framework. Results The review will identify and map global experiences in the use of ICTs in primary care for NCDs and assess their impact on the quality of care in PHC. It is hoped to find studies that address the use of digital technologies for early detection, management and follow-up of NCDs, as well as their integration with traditional health systems. Conclusions The integration of digital technologies into PHC has the potential to improve the quality of care, but it can also accentuate inequities. It is necessary to consider digital health literacy, access to tools, and legal and ethical aspects of data protection. The review will highlight the need for robust policies and adequate infrastructure to support the effective implementation of digital health in PHC.